Cold‐conveyor‐belt jet, sting jet and slantwise circulations in idealized simulations of extratropical cyclones. (21st April 2016) - Coronel, B.; Ricard, D.; Rivière, G.; Arbogast, P.
Abstract : The present study investigates the formation of sting‐jet cyclones using an idealized configuration of a high‐resolution mesoscale numerical model. The initial set‐up is composed of axisymmetric finite‐amplitude synoptic‐scale cyclones added to a baroclinic zonal jet. When the surface cyclone is initialized on the warm‐air side of the zonal jet, a strong bent‐back warm front forms, which is a favourable condition for sting jets. A rather high vertical resolution of about 200 m in the lower troposphere is required to obtain well‐formed slantwise circulations near the cloud head and to make the distinction between cold‐conveyor‐belt jet and sting jet. In contrast, when the surface cyclone is initialized on the jet axis, the surface cyclone is more representative of the Norwegian cyclone model and the bent‐back warm front is almost non‐existent. Sting‐jet mechanisms are analyzed using backward Lagrangian trajectories. A minority group of air parcels entering the sting‐jet region undergoes diabatic cooling due to sublimation of snow and graupel. The majority group does not present such a diabatic cooling and corresponds to descending air masses from the cloud‐head region in a near‐neutral environment with respect to conditional symmetric instability. Indeed, the saturated moist potential vorticity is near zero and the momentum surfaces and saturated moist isentropes are quasi‐parallel in the main slantwise descent. The latter descent is shown to be geostrophically forced by the strong divergent component of the along‐front Q vector. Boundary‐layer processes are also analyzed. In most areas, the static stability being strong, there is no penetration of descents coming from the sting jet into the boundary layer and the peaks in surface wind gusts are connected to intrinsic boundary‐layer convective cells and parametrized turbulence. Such a penetration occurs in some areas but is not related to the strongest wind gusts.